A comparative performance analysis and thermo-sustainability indicators of modified low-heat organic Rankine cycles (ORCs): An exergy-based procedure. (November 2018) - Abam, F.I.; Ekwe, E.B.; Effiom, S.O.; Ndukwu, M.C.
Abstract: The paper presents a comparative analysis of thermo-sustainability indicators (TSIs) and performance of organic Rankine cycles (ORCs) with different working fluids. The objective of the study is to determine the sustainability of the ORCs using R245fa, R1234yf, and R1234ze refrigerants. The ORC configurations include the ORC-basic (ORCB), ORC-internal heat exchanger (ORCIHE), ORC-turbine bleeding (ORCTB), and ORC-turbine bleeding/regeneration (ORCTBR). The TSI evaluated comprise overall exergy efficiency (OEF), exergy waste ratio (EWR), and environmental effect factor (EEF) in addition to exergetic sustainability index (ESI). The results indicate that the OEF obtained using R245fa fluctuated between 30 . 26 ≤ OEF ≤ 38 . 82 with 8.56% efficiency difference between ORCB and ORCTBR at evaporator pressure (EVP) of 2 and 3 MPa. The ESI values were maximum with R245fa while EEF values of 1.5 and 1.58 were obtained at same EVP range. Additionally, the ORCTBR and ORCTB had the least environmental impact and were ecologically stable with R245fa than R1234yf, and R1234ze. In conclusion, the performance of the ORCs is dependent on the following: working fluid, system configuration and operating conditions. Thus optimum conditions for each working fluid for a particular system configuration is central to achieving environmental stability.